Sexual harassment and gender discrimination - Ali Mohamed, Ashgar Ali; Sardar Baig, Farheen Baig (2015)
Sexual harassment refers to any unwanted or unwelcomed conduct of a sexual nature either verbal, non-verbal, visual, psychological or physical harassment. As sexual harassment violates an individual’s fundamental rights, the perpetrator may be subject to criminal prosecution besides a range of disciplinary measures, up to and including dismissal from employment. Further, such offensive conduct has the tendency of creating an intimidating, hostile and offensive work environment which can adversely affect the industrial relations climate in the organisation. Sexual harassment comes within the ambit of gender discrimination. In quid pro quo harassment a tangible loss is involved where the superior with authority to approve job assignment, evaluation and benefits, solicits sexual favours as a prerequisite of getting such benefits. If the unfavourable treatment was due to the employee’s refusal to accede to the sexual demands, it may well fall within the scope of the gender discrimination. Similarly, terminating victim’s employment contract merely because the victim could not withstand conducts of sexual harassment at the workplace comes also within the scope of gender discrimination. Hence, the issue of sexual harassment and gender discrimination in the context of Malaysian law and practice forms the basis of this paper.